Blunting Stress Response During Intubation in Hypertensive Patients; A Comparison Between Lidocaine and Magnesium Sulphate - Feroze, Rehana; Hussain, Aftab; Naseer, Mehwish (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare blunting of hemodynamic stress response to intubation using Magnesium Sulphate versus Lidocaine in hypertensive patients. Study Design: Prospective comparative study. Place and Duration of Study: Anaesthesia Department Combined Military Hospital, Lahore Pakistan, from Jan to Jun 2019. Methodology: A total of 232 hypertensive patients of the ASA status II, undergoing elective surgical procedures requiring intubation, were randomly divided into two groups, Group-L (Lidocaine) and Group-M (Magnesium Sulphate). Lidocaine 1.5mg/kg was given to Group-L 90 seconds before laryngoscopy, whereas Magnesium Sulphate 30mg/kg was given over ten minutes to Group-M before laryngoscopy. Baseline means arterial pressure was recorded. Mean arterial pressure was subsequently recorded each minute after intubation for five minutes. Results: Both groups were similar with regard to demographic data. After intubation, both groups had an increase in mean arterial pressures. Blunting of stress response was observed in 78 patients (67.2%) in Group-L and 55 patients (47.4%) in Group-M. Two groups showed a significant statistical difference (p=0.003). Conclusion: Both drugs are effective in blunting hemodynamic stress response to intubation in hypertensive patients, but Lidocaine is more effective than Magnesium Sulphate.